2023
DOI: 10.1039/d3dt02821f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one-pot syntheses of secondary amines from nitro aromatics and benzyl alcohols over Pd/NiTi-LDH under visible light

Jiaqi Wang,
Jiaqi Jiang,
Zhaohui Li

Abstract: Visible light-initiated one-pot syntheses of secondary amines from the reaction between nitro aromatics and alcohols are realized over Pd/NiTi-LDH via a successful coupling of LDH-based photocatalysis and Pd-based hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The Lewis acidic sites derived from LDH provide active sites for isomerization, while photocatalysis achieves selective cleavage of C-C bonds by regulating the generation of reactive oxygen species. Wang et al prepared Pd/NiTi•LDH nanocomposites by loading small Pd nanoparticles onto NiTi•LDH nanosheets for efficient one pot synthesis of secondary amines under visible light [69]. In previous studies, NiTi LDHs have been shown to exhibit excellent photocatalytic performance due to their abundant surface oxygen defects.…”
Section: Original Ldh Catalystsmentioning
confidence: 99%
“…The Lewis acidic sites derived from LDH provide active sites for isomerization, while photocatalysis achieves selective cleavage of C-C bonds by regulating the generation of reactive oxygen species. Wang et al prepared Pd/NiTi•LDH nanocomposites by loading small Pd nanoparticles onto NiTi•LDH nanosheets for efficient one pot synthesis of secondary amines under visible light [69]. In previous studies, NiTi LDHs have been shown to exhibit excellent photocatalytic performance due to their abundant surface oxygen defects.…”
Section: Original Ldh Catalystsmentioning
confidence: 99%